A Study on Multipole BLDC Sensorless Control Methods based on Integration of Non-excited Phase Back-EMF - Park, Jin-Wook; Hwang, Myeong-Hwan; Kim, Dong-Hyeon; Cha, Hyun-Rok; Park, Sung-Jun; Park, Seong-Mi (International Journal of Engineering and Technology, 2018)
Background/Objectives: As multipolar electric motors have been widely used recently, studies on high-capacity multipole BLDC sensorless control methods have attracted attention.Methods/Statistical analysis: There is a compelling need for stable sensorless control methods because high-capacity multipole BLDC motors by multipolarization has a high frequency of voltage applied by high-speed operation. Therefore, in this paper we proposed a new sensorless control method for counter electromotive force in the non-conducting periods on both sides of the conducting periods of BLDC motors driven in the 120Â° conduction mode. The proposed sensorless control method switches to integrate counter electromotive force in the non-conducting period and to control the values. In addition, this paper tested the validity of the proposed method for 4 kw-class 28-pole BLDC motors.Findings: The proposed method made it possible to realize sensorless strongly resistant to noise by realizing sensorless based on integrating counter electromotive force.To control the ratio of the integrated values of counter electromotive force makes it possible to adjust switching periods and to realize various controls such as field-weakening control.Improvements/Applications: It can be used in the case of multi-pole high-speed operation, It is expected that it will be widely used for drone BLDC motor and electric kickboard which is difficult to install position sensor.Â Â